2020
DOI: 10.1111/apt.15732
|View full text |Cite
|
Sign up to set email alerts
|

Profiles of serum soluble programmed death‐1 and programmed death‐ligand 1 levels in chronic hepatitis B virus‐infected patients with different disease phases and after anti‐viral treatment

Abstract: Background: Soluble programmed death-1 (sPD-1) and soluble programmed deathligand 1 (sPD-L1) play a role in immune regulation of chronic hepatitis B virus (HBV) infection. Aim: To investigate the profiles of serum sPD-1 and sPD-L1 in chronic HBV-infected patients with different disease phases and after anti-viral treatment. Methods: A total of 99 chronic HBV-infected patients were enrolled and divided into HBeAg-positive chronic HBV infection (EPI) group, HBeAg-positive chronic hepatitis B (EPH) group, HBeAg-n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
14
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 29 publications
5
14
2
Order By: Relevance
“…However, their research showed similar results that patients with CHB had higher levels of sPD-1 than healthy controls. Consistent with Xia et al [ 11 ], our results showed that the sPD-1 levels were positively correlated with ALT and HBV DNA levels at 6 and 12 mo. The sPD-1 levels decreased in all patients after baseline, which might be associated with lower viral load and lower expression of viral antigen after antiviral treatment.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…However, their research showed similar results that patients with CHB had higher levels of sPD-1 than healthy controls. Consistent with Xia et al [ 11 ], our results showed that the sPD-1 levels were positively correlated with ALT and HBV DNA levels at 6 and 12 mo. The sPD-1 levels decreased in all patients after baseline, which might be associated with lower viral load and lower expression of viral antigen after antiviral treatment.…”
Section: Discussionsupporting
confidence: 93%
“…Different ELISA kits could contribute to discrepant results. Xia et al [ 11 ] used different ELISA kits for dosing sPD-1 Levels. There was a significant correlation between the sPD-1 levels and ALT levels at baseline in Zhou et al [ 9 ], but a weak correlation in Xia et al [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Increased serum sPD-L1 levels in chronic HBV infection, especially in the first step from health to infection, are in agreement with the latest report [32], the PD-1/PD-L1 axis serving as a negative immune regulator and HBV-induced expression of PD-1 and PD-L1 [8][9][10][11][12][13][14][15][16][17]. The positive correlation between serum sPD-L1 and HBsAg further supports the effect of the PD-1/PD-L1 axis on the chronicity of HBV infection.…”
Section: Discussionsupporting
confidence: 92%
“…We thank Dr Vyas for his interest in our study on the profiles of serum soluble programmed death‐1 (sPD‐1) and programmed death‐ligand 1 (sPDL‐1) levels in chronic hepatitis B virus (HBV)‐infected patients with different disease phases and during anti‐viral treatment 1,2 . The letter raises several interesting points deserving clarification.…”
mentioning
confidence: 99%